The Role of Indonesian Muslim Entrepreneurs Community for Home Industry Players in Empowering Women During the Pandemic - Darlin Rizki; Fauzul Hanif Noor Athief; Mega Atika; Annisa ul Lathifah (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
The occurrence of a pandemic (Covid-19) resulted in many changes, especially in the economy of the people who became unstable. The women's empowerment community is one of the organizations that provides a platform for women who want to help improve the economy of their families. So this study aims to find out how big the role of a Muslim community in Indonesia is and its impact on empowering women in home-based industrial businesses which experienced a drastic decline during the COVID-19 pandemic. This research uses a qualitative research type. Data was collected through observation, interviews and documentation. Based on the research that the author conducted at the Indonesian Muslim Entrepreneurs Association, it shows that Indonesian Muslim Entrepreneurs Association has various major programs that aim to be able to advance and help enlighten Muslim entrepreneurs. They have played an active role in empowering women in which in carrying out their activities good morals are the main focus in attracting members. Because in entrepreneurship besides having to be good at looking for relationships and opportunities, of course it also requires good ethics. So that the marketing network becomes wider, and the knowledge and skills increase.